2020
DOI: 10.1016/j.dib.2020.106018
|View full text |Cite
|
Sign up to set email alerts
|

Data on the impact of socioeconomic status on academic achievement among students in Malaysian public universities

Abstract: This data article presents the impact of parents' socioeconomic status on undergraduate students’ academic achievements at a Malaysian higher education institution. The eastern parts of Peninsular Malaysia are populated by low-income citizens compared to the national average. The survey was conducted in Universiti Malaysia Terengganu. The targeted population is final year social science students. The total size of the target population is 965 students. Using Krejcie and Morgan's sampling method, a sample size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Further, female students exceeded the number of male students in the sample which could be attributed to the greater number of females in the sample frame. Similar trend is reported in many studies conducted on university students in Malaysia (27). Regarding ethnicity, the sample had representation from all major ethnic groups in Malaysia (28).…”
Section: Discussionsupporting
confidence: 83%
“…Further, female students exceeded the number of male students in the sample which could be attributed to the greater number of females in the sample frame. Similar trend is reported in many studies conducted on university students in Malaysia (27). Regarding ethnicity, the sample had representation from all major ethnic groups in Malaysia (28).…”
Section: Discussionsupporting
confidence: 83%
“…The B40 refers to households with monthly income below RM4,360 (≈ USD 976). As observed by Sulaiman et al (2020), the families of most university students in Malaysia fall into this income category. Universities or colleges in Malaysia are mostly concentrated in the city, thus requiring the migration of rural students who are foreign to the affluent urban culture.…”
Section: Theoretical Frameworkmentioning
confidence: 90%
“…Participants in this study were students from Malaysian public universities who belong to B40-income households. Most students in public universities in Malaysia are from families of B40 income category (Sulaiman et al, 2020). Other inclusion criteria include being unemployed, unmarried, and dependent on family income or education scholarships or loans for sustenance.…”
Section: Methodology Participants and Survey Methodsmentioning
confidence: 99%
“…During the preschool period, scholars have shown that kindergarten-age children from wealthier families achieve better cognitive and emotional development than those from poorer families (Christensen et al, 2014 ; Lurie et al, 2021; Zhang et al, 2019 ). Moreover, a body of research suggests that the disparities in academic achievement due to family background persist in primary school (von Stumm et al, 2020 ; Waters et al, 2021 ), secondary school (Van de Werfhotst, 2018 ; van Zwieten et al, 2021 ), high school (Barr, 2015 ; Reeves, 2012 ), and even university (Destin et al, 2019 ; Sulaiman et al, 2020 ). These results are consistent in developed countries (Daniele, 2021 ; von Stumm, 2017 ) and developing countries (Dolean et al, 2019 ; Iruka et al, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%